Rektionskomposita im Deutschen und im Chinesischen - Yang, Yaqing (Studia Germanica Posnaniensia, 2019)
The subject of this article are nominal compounds in German and Chinese which are assigned to the class of synthetic compounds. Such compounds are based on a verb stem, to which are added lexical morphemes and/or suffixes anchored in the grammar and semantics of the (verbal) head. In German, the verb with the suffix forms a derivative which, as the basic word, selects an argument (object or subject) in function of the determinative word. In this way, a government relationship is established between the constituents of the compound. This applies equally to action nouns and agent nouns. In Chinese, there are not formal exponents of the action noun, so the analysis had to be limited to agent nouns. In their derivation, the verb stem and its object mostly form a constituent that acts as a complement of the agent exponent. The examination of such synthetic compounds is carried out from the perspective of the argument.